GETTING TO KNOW YAHOWU AND YA’AHOWU WARM GREETINGS FROM THE NIAS COMMUNITY - Harefa, Darmawan (Universitas Nias Raya, 2025)
Language and culture play a crucial role in shaping the identity of a community. In Nias society, the greetings